A genetic algorithm with tournament selection for optimising inspection allocation in multiproduct multistage production systems. (9th January 2012) - Korytkowski, Przemyslaw
Multiproduct multistage production systems have been widely implemented in recent years. One of the important considerations in such systems is identifying the location of inspection stations. This paper considers a multiproduct setting where part types compete with each other for common production resources. In this environment, it is important to consider factors such as throughput time variability and to include the corresponding queuing aspects into the model. Each workstation is modelled as a GI/G/c queue. The optimal allocation is determined by using a genetic algorithm with tournament selection, one–point crossover and uniform mutation.